Influence of Interest Groups on the Development of Public Policy of Renewable Energy in Lithuania 2008-2018 - Jatautas, Jaunius; Stasiukynas, Andrius (Socialiniai tyrimai, 2019)
Interest groups play an important role in public policy-making and decision-making in public sector governance. While abroad, interest groups have been extensively analysed by scholars, but the assessment of the influence of interest group activities on public policymaking in Lithuania is insufficient. The problem of the research is that this field has not been thoroughly analysed until now. There is no universally agreed and defined definition about kind of activity of interest group and its influence in Lithuania. Thus, in the context of existing research, there is a need for a deeper insight into the activities of interest groups with a focus on assessing their impact on public governance. The object of this article is interest groups and their activities in the Lithuanian renewable energy (RE) sector. The aim of the research described in this article is to investigate the interest groups acting in the RE sector and the influence of the activities on public policy-making in 2008–2018. Authors, based on the functions of interest groups, distinguish the main principles of their activities: to properly analyse the situation, to express themselves publicly and to communicate with society, to form a positive attitude, which would be accepted by both the interest group and the society. In addition, interest groups communicate directly with government officials, attend public hearings, report on current political issues, and appear in the media. Involvement of interest groups can be defined as the process by which interest groups or their representatives, together with officials, are involved in raising issues of major importance to society, formulating policy, discussing and deciding on issues relevant to the management of the RE sector. It can be argued that although the public policy is formulated and implemented by public authorities during the public governance process, there are various interest parties involved at different stages of the process. They can formally become influential interest groups according to the value of their influence and the relevance of the issue. All interested parties have an opportunity to participate in the process of developing the legal framework, but the proposals of all of them are not considered due to the aspect of renewable energy. There is no unified database in Lithuania, which contains all interest groups acting in Lithuania. Therefore, it is necessary to typologize them. The typology is based on Kaunas University of Technology scientists’ group project 2015–2017: Interaction between parties and interest groups: nature, causes, consequences, according to the specifics of the Lithuanian RE sector. In order to investigate the activities of the interest groups, the methods of document analysis and descriptive statistics were applied. Comprehensive data collection and systematisation was carried out on the basis of the Seimas committees’ meeting documents, and on the basis of the received analysis data, typology of interest groups and their impact assessment was performed. In order to find out the involvement of interest groups in the public-governance of the ER sector, the analysis of meetings of the Seimas committees and commissions in 2008–2019 was carried out. During the period 2007–2010, issues relevant to the RE sector were discussed. In the documents of meetings invited persons and those who actively made proposals have been highlighted, thus identifying interest groups. In the second stage of research, based on the typology presented in the article earlier, interest groups were categorized by adapting the table accordingly to the interest groups involved in public governance in the RE sector. The third stage identifies the most influential interest groups acting in the public sector of the RE, according to the number (activity) of proposals submitted to the draft laws and accordingly the number of submitted proposals. This is how the percentage of influence was derived. As the results of the research have shown, that interest groups have the greatest influence in the public government process of the RE sector at the stage of public policy making. However, the balancing of interests does not produce the desired results due to insufficient influence of the interest group. By researching the activities of interest groups in the RE sector policy making stage, types of interest groups can be established according to their members’ goals, activities, aspirations, and relationships. After research of the Seimas activities in 2008–2018 related to activities in RE policy-making, it can be stated that the public administration organizations and their associations are most active interest groups in submitting amendments to the law. They have submitted 867 proposals during the analysed period. Members of the Seimas have submitted 414 proposals. During the period which was under review, 250 business proposals were submitted by business interest groups and only 28 by public interest groups.